The Event called Ocean Merce Cunningham dancer Jeannie Steele in conversation - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 2006)
Merce Cunningham dancer Jeannie Steele in conversation PALABRAS CLAVE: Merce Cunningham Dance Company, Jeannie Steele, Ocean.